Transformasi Pembelajaran Matematika di Sekolah Dasar Melalui Pendekatan Dilemma Story Pedagogy - Ikamaya Sridarma Dewi; Neni Mariana; Rooselyna Ekawati (Cetta: Jurnal Ilmu Pendidikan, 2023)
Humans grow and develop so can freely learn according to their wishes to change views to be broader, and learning mathematics is no exception. Learning mathematics is closely related to life, but reality is contrary to the situation on the ground. Mathematics learning based on open without any approach to life's problems. This research explore experiences related to life's problems through critical reflection within oneself, so moral dilemma story emerges and can change one's views regarding mathematics learning in elementary schools through the dilemma story pedagogy. Type of this research uses qualitative-transformative, understanding and experiences related to oneself and relationships with life's problems that can influence views on learning mathematics. The method used is auto |ethnography with several paradigms include interpretive, critical, and post-modern paradigms. The research instrument of the researcher themself as the main data source, literature studies and semi-structured interviews. Research subjects included researchers, class teachers, and fifth grade elementary school students. Data analysis in this research uses five ways knowing, starting from cultural self-knowing, relational knowing, critical knowing, visionary and ethical knowing, and then knowing in action. The results showed that analysis of cultural identity data of researchers and research subjects as students who had studied mathematics and experienced life's dilemmas influence the transformation of views to learning mathematics which was frightening become fun through the dilemma story pedagogy approach. Resulting in changes in the views of both researchers and participants including readers regarding the understanding of learning mathematics in elementary schools with the dilemma story pedagogy.